Work Environment Characteristics and Emotional Intelligence as Correlates of Nurses' Compassion Satisfaction and Compassion Fatigue: A Cross-Sectional Survey Study - Stephanie Maillet; Emily Read (MDPI AG, 2021)
This cross-sectional survey study examined the relationship between Canadian nurses' work environment characteristics, emotional intelligence, compassion fatigue and compassion satisfaction (n = 1271). Psychological demands, decision latitude, supervisor and coworker support, and emotional intelligence (EI) were significantly correlated with nurses' compassion satisfaction and compassion fatigue, except for two EI subscales. Furthermore, these relationships were stronger for compassion satisfaction than compassion fatigue, suggesting that they are influenced by different factors. Our results highlight the importance of creating reasonable psychological demands, empowering nurses to make decisions in their jobs, supportive relationships at work, and fostering the development of nurses' EI.